RETRACTED: Estimation of the effect of catalyst physical characteristics on Fenton-like oxidation efficiency using adaptive neuro-fuzzy computing technique. (January 2015) - Rahim Pouran, Shima; Abdul Aziz, A.R.; Wan Daud, Wan Mohd Ashri; Shamshirband, Shahaboddin
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (http://www.elsevier.com/locate/withdrawalpolicy ). This article has been retracted at the request of the Editor-in-Chief. After a thorough investigation, the Editor has concluded that the acceptance of this article was based upon the positive advice of four faked reviewer reports. The reports were submitted from fictitious email accounts which were provided to the journal as suggested reviewers during the submission of the article. Journal records indicate that confirmation of the submission and publication of the article was sent to the email address that used the name of the author S. Shamshirband. This manipulation of the peer-review process represents a clear violation of the fundamentals of peer review, our publishing policies, and publishing ethics standards. Apologies are offered to the readers of the journal that this deception was not detected during the submission process.